PENINGKATAN KESEHATAN IBU HAMIL MELALUI CONTINUITY OF CARE (COC) BERBASIS PROGRAM YOGITA DI PUSKESMAS KEDUNGWUNGU - Amalia, Silviatul; Kurniawati, Septi; Wati, Emita Dewi Lilis Angkasa; Sari, Rina Yunita Dewi; Matriyani, Ririn; Rafflesiani, Fista (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
Maternal mortality in Indonesia remains at 140 per 100,000 live births in 2023, indicating the ongoing need to strengthen promotive and preventive efforts for pregnant women. Limited implementation of Continuity of Care (CoC), inadequate physical activity, and suboptimal nutritional intake contribute to increased maternal health risks. This community service activity aimed to improve maternal health through the YOGITA Program (Yoga Ibu Tangguh & Asupan Gizi Tepat), which is based on a Continuity of Care approach. The program methods included CoC-based mentoring, prenatal yoga classes, and nutritional education delivered to 25 pregnant women in their second and third trimesters within the working area of Kedungwungu Primary Health Center. Data were collected using knowledge questionnaires, mid-upper arm circumference (MUAC) measurements, hemoglobin level assessments, as well as observations and brief interviews conducted before and after the intervention. The results demonstrated an improvement in maternal knowledge, with the proportion of participants in the “good” category increasing from 76% to 92% following the intervention. Maternal nutritional status was predominantly classified as good, as indicated by normal MUAC in 88% of participants and non-anemic status in 92%. In addition, participants reported improved physical fitness, relaxation, and readiness for childbirth. Program outputs included enhanced maternal capacity, the development of nutritional education posters, and a community-based prenatal yoga class model. This activity contributes to strengthening promotive maternal health efforts through a holistic and sustainable approach and has the potential to be replicated in other primary health care settings.